A novel variant in CMAH is associated with blood type AB in Ragdoll cats - Gandolfi, B.; Grahn, R. A.; Gustafson, N. A.; Proverbio, D.; Spada, E.; Adhikari, B.; Cheng, J.; Andrews, Gordon; Lyons, L. A.; Helps, C. R. (My University, 2016)
The enzyme cytidine monophospho-N-acetylneuraminic acid hydroxylase is associated with the production of sialic acids on cat red blood cells. The cat has one major blood group with three serotypes; the most common blood type A being dominant to type B. A third rare blood type is known as AB and has an unclear mode of inheritance. Cat blood type antigens are defined, with N-glycolylneuraminic acid being associated with type A and N-acetylneuraminic acid with type B. Blood type AB is serologically characterized by agglutination using typing reagents directed against both A and B epitopes. While a genetic characterization of blood type B has been achieved, the rare type AB serotype remains genetically uncharacterized. A genome-wide association study in Ragdoll cats (22 cases and 15 controls) detected a significant association between blood type AB and SNPs on cat chromosome B2, with the most highly associated SNP being at position 4,487,432 near the candidate gene cytidine monophospho-N-acetylneuraminic acid hydroxylase. A novel variant, c.364C>T, was identified that is highly associated with blood type AB in Ragdoll cats and, to a lesser degree, with type AB in random bred cats. The newly identified variant is probably linked with blood type AB in Ragdoll cats, and is associated with the expression of both antigens (N-glycolylneuraminic acid and N-acetylneuraminic acid) on the red blood cell membrane. Other variants, not identified by this work, are likely to be associated with blood type AB in other breeds of cat. © 2016 Gandolfi et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Citation: Gandolfi, B., Grahn, R. A., Gustafson, N. A., Proverbio, D., Spada, E., Adhikari, B., . . . Helps, C. R. (2016). A novel variant in CMAH is associated with blood type AB in Ragdoll cats. Plos One, 11(5). doi:10.1371/journal.pone.0154973